The Influence of Work Motivation and Job Satisfaction on Teacher’s Performance - Putria, Syafwatul; Lian, Bukman; Kristiawan, Muhammad (Journal of Social Work and Science Education, 2024)
The aim to be achieved in this research is to determine the level of influence of motivation and job satisfaction on teacher’s performance and to determine the level of influence of work motivation and job satisfaction on teacher’s performance together with teacher teaching performance. This research was conducted at SMP Negeri 12 Palembang, SMP Negeri 25 Palembang, and SMP Negeri 36 Palembang located in Kertapati District, Palembang. This research uses a correlational (cause-and-effect) quantitative research model with a population of 3 schools totaling 151 people and a sample of 60 people. To obtain the data needed in this research, several techniques were used, namely questionnaires, observation, and documentation. Based on the results of the data analysis, the following can be concluded. There is an influence of work motivation on teacher’s performance. This means that the higher the teacher’s work motivation, the more the teacher’s performance will increase. There is an influence of Job Satisfaction on Teacher’s performance. This means that the higher the job satisfaction, the higher the teacher’s performance will be. There is an influence of work motivation and job satisfaction on teacher’s performance. Thus, work motivation and job satisfaction can influence teacher’s performance. Work motivation and job satisfaction can influence teacher’s performance with a contribution of 80.5% while the remaining 19.5% is explained by factors not examined in this research.